2017
DOI: 10.1002/2016wr019661
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying spatial groundwater dependence in peatlands through a distributed isotope mass balance approach

Abstract: The unique biodiversity and plant composition of peatlands rely on a mix of different water sources: precipitation, runoff, and groundwater (GW). Methods used to delineate areas of ecosystem groundwater dependence, such as vegetation mapping and solute tracer studies, are indirect and lack the potential to assess temporal changes in hydrology, information needed in GW management. This paper outlines a new methodology for mapping groundwater‐dependent areas (GDAs) in peatlands using a 2H and 18O isotope mass ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 44 publications
7
23
0
Order By: Relevance
“…Since periods of high flow tend to be isotopically similar to recent precipitation (von Freyberg et al, 2018), we compared flow-weighted and unweighted river water lines. Furthermore, we also calculated Local River Water Lines (LRWL) representing local precipitation and evaporation processes, which are influenced by local climate, geology, and landcover (Isokangas et al, 2017) for each sampling site. Where multiple sites were located within the same connected river network, we compared LRWLs for upstream and downstream sites.…”
Section: Discussionmentioning
confidence: 99%
“…Since periods of high flow tend to be isotopically similar to recent precipitation (von Freyberg et al, 2018), we compared flow-weighted and unweighted river water lines. Furthermore, we also calculated Local River Water Lines (LRWL) representing local precipitation and evaporation processes, which are influenced by local climate, geology, and landcover (Isokangas et al, 2017) for each sampling site. Where multiple sites were located within the same connected river network, we compared LRWLs for upstream and downstream sites.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent findings about kinetic fractionation in the water pools and tracks of an extended drainage network in a raised bog within the Bruntland Burn showed that evaporation can have a fractionating effect on the stable isotopes of peatland waters, despite the relatively low energy available (Sprenger et al, 2017b). While such isotopic fractionation of open waters in peatlands of the northern latitude were found by others (Carrer et al, 2016;Gibson et al, 2000;Isokangas et al, 2017), the potential fractionation dynamics of the water in the upper soil layer in these cold regions have not previously been studied.…”
Section: Introductionmentioning
confidence: 93%
“…These techniques, applicable for peatland sites, include conventional direct hydrological measurements (use of piezometers, slug tests, boreholes, etc.) (Johansen et al, 2011; Rossi et al, 2012), thermal imaging and other remote sensing techniques (Bechtold et al, 2018; Briggs et al, 2016; Hare et al, 2015, 2017), geophysical measurements (Lowry et al, 2009; McLachlan et al, 2017), and use of natural tracers, including stable water isotopes (Isokangas et al, 2017; Levy et al, 2014, 2016; Négrel et al, 2010). These methods provide valuable information on the current state of GW‐SW connectivity but are of little use in predicting how the system will react to changing conditions, such as groundwater abstraction, changes in land use, or climate change.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no rigorous framework on how to represent peat soils in fully integrated GW‐SW models. Peat soils have highly heterogeneous properties (Baird et al, 2008; Beckwith et al, 2003; Holden & Burt, 2003; Isokangas et al, 2017; Lewis et al, 2012; Päivänen, 1973; Rosa & Larocque, 2008) and are thus difficult to represent in numerical models. Field studies have shown that factors such as preferential flow paths (Holden & Burt, 2002; Lowry et al, 2009), hydraulic conductivity (Drexler et al, 1999; Hare et al, 2017), and abrupt changes in peat thickness (Hare et al, 2017; Lowry et al, 2009) may affect the location of groundwater discharge.…”
Section: Introductionmentioning
confidence: 99%